Kajian Mutu Fisik, Kimia dan Mikrobiologi Gula Aren BumbungMenggunakan Metode Studi Deskriptif Komparatif: Study of Physical, Chemical and Microbiological Qualities of Bumbung Palm Sugar Using A Descriptive Comparative Method - Rastika, Ketut Deta; Handayani, Baiq Rien; Amaro, Moegiratul; Jannah, Mirriyadhil (Universitas Bumigora, 2025)
Bumbung palm sugar is gaining popularity as a natural sweetener; however, its quality remains inconsistent and often falls short of national standards. This inconsistency is likely due to varying processing practices across production sites. However, comparative studies among different villages are still limited. This study aimed to evaluate the physical, chemical, and microbiological quality of bumbung palm sugar produced in five hamlets of Kekait Village. A descriptive-comparative approach was used with direct sampling from producers, followed by laboratory analysis. Data were analyzed using analysis of variance (ANOVA) at a 5% significance level and followed by an Honestly Significant Difference (HSD) test. Results showed that production location significantly affected texture, moisture content, and sucrose level (p < 0.05), but not color or pH. Kekait Puncang had the highest yeast count (2.65 × 107 CFU/g), while mold (<1.0 × 102 CFU/g) and total microbial counts (<1.0 × 104 CFU/g) showed no significant differences. Palm sugar from Batu Butir best met the Indonesian National Standard (SNI) for color (reddish), moisture (9.3%), and sucrose (79.05%), followed by products from Kekait II and Thaebah. In conclusion, Batu Butir produced the highest-quality product. This study provides a basis for quality improvement and local agroindustry development of palm sugar.